Direct Detection of the Photorearrangement Reaction of Quinoline‐Protected Dialkylanilines. (2nd December 2021) - Liang, Runhui; Lan, Xin; Asad, Naeem; Dore, Timothy M.; Zhang, Qidi; Du, Lili; Phillips, David Lee
ABSTRACT: The photolysis reactions of (8‐cyano‐7‐hydroxyquinolin‐2‐yl)methyl (CyHQ)‐caged amines have been investigated using time‐resolved spectroscopy methods. Unexpectedly, an unconventional Hofmann‐Martius rearrangement reaction with high yield and regioselectivity occurred during the photolysis of some CyHQ‐protected dialkylanilines (such as compounds 1a and 2a). To have more insights into the mechanism of this unexpected photorearrangement reaction, we characterized the reaction intermediates directly using time‐resolved spectroscopy. Our new results showed that the anionic form of compound 1a was photoexcited to the singlet excited state, then a heterolytic cleavage of the C‐N bond took place to give CyHQ + and the corresponding aniline. Thereafter, the recombined intermediate 6 was found to appear in about 19.7 and 44.3 ps for 1a (A) and 2a (A), respectively, before the generation of an ortho ‐substituted aniline (1b and 2b) via the excited‐state deprotonation of 6. Thus, a logical photodynamic mechanism of this photoinduced Hofmann‐Martius rearrangement reaction was deduced. This new insight into the reaction mechanisms may be helpful for the design of novel related photoactivatable aniline molecules and for understanding other similar photorearrangement reaction mechanisms. Abstract : Femtosecond and nanosecond time‐resolved transient absorption (fs‐TA and ns‐TA) spectra were obtained to investigate the reaction mechanism of an intriguing Hofmann‐Martius photorearrangement reaction that occurred after photoexcitation of some (8‐cyano‐7‐hydroxyquinolin‐2‐yl)methyl (CyHQ)‐protected dialkylanilines. The heterolysis of the C‐N bond was found to take place in around 2.5 ps to generate the CyHQ + and the corresponding aniline in their singlet excited states. Then, they recombined in around 19 ps to produce the singlet excited state of the recombined species as observed in the fs‐TA experiments and supported by results from quantum chemical calculations.